PENERAPAN MODEL PEMBELAJARAN ASSURE DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Rifqi Hidayat; Sumliyah sumliyah; Indriyani Indriyani (EduMa: Mathematics education learning and teaching, 2017)
The research is based on the law of critical thinking and the less of the studentsâ€™s activation in learning process. The research objective is to know the improvement of critical thingking which the learning process used is ASSURE learning model with conventional learning. The research is Quasi Experimental research.The research design is used Nonequivalent Control Group Design and sample collection technique is Sampling Purposive .The population in the research is the students of class 8th Â SMPN 1 Sumber Kabupaten Cirebon, academic year 2017/2018. The sample of the research is the 8th qraders 36 th student class 8th D is classes eksperimental and 38 th student class 8th F is classes control. Based on the result of the difference of the average of post-test using the test of Independent Sample T-Test equals sig (2 tailed) score 0,000 < 0,05 means H0 rejected. And then the difference of the average using of N-gain using the test of Independent Sample t-test equals sig score (1 tiled) 0,0005 < 0,05 means H0 rejected. On the other hard, based on the result of questionnaire using the test of Mann Whitney U-Test eguals Asymp. Sig(2 tailed) 0,000 < 0,5 means H0 rejected. The research result shows that: The improvement of critical thinking skill which is using ASSURE learning model is better than the students who are learning by conventional learning process.Key Words: ASSURE, Critical Thinking